A diagnostic study on livestock production system in Eastern Region of India - GUPTA, J J; SINGH, K M; BHATT, B P; DEY, A (The Indian Journal of Animal Sciences, 2014)
A study was conducted in seven east Indian states to understand the livestock production and management systems for making strategies for the improving livestock production. The data were collected from 2 districts from each state and from each district 25 farmers, on socio-economic status of farmers, animal status, feeding system, health status, breeding methods, assistance needs etc. Family size varied from 5.31 (West Bengal) to 9.48 (eastern Uttar Pradesh) and mostly heads of families were educated having more than 0.5 ha of agriculture land. The majority (70.86%) of the farmers were not able to spare agriculture land for fodder production. A large number of farmers in Asom, Chhattisgarh and Jharkhand had non-descript cows. However, the majority of farmers surveyed in Bihar and eastern Uttar Pradesh had crossbred cow. Average milk production (kg/d), lactation length (m) and dry period (m) amongst animals of eastern region for non-descripts cows 2.48, 7.71, and 6.66, for crossbred cows 7.20, 9.08, and 3.85 and for buffaloes 5.54, 8.56, and 6.93, respectively. The majority of the farmers of the region reported foot-and-mouth disease (FMD) as a major concern and were not satisfied with their animals and production. It can be concluded that livestock farmers of the region are in great need of improved breeds, capacity building on balance feeding and general management practices for better and sustainable animal production.